Composing Digital Multimodal Notices Using the InShot Application as Learning Media - Vina Nurviyani; Luthfita Aulia Dewia (Muhammadiyah University of Mataram, 2022)
Digital technology has become very influential globally, particularly in developing learners' writing skills. This study investigated the implementation of the InShot application in creating digital multimodal notices. Moreover, it explored the strengths and weaknesses of the InShot app applied as the learning media in composing digital multimodal notices. The study used qualitative design (a case study) involving 27 students studying at a junior high school in West Java. Observations, open-ended questionnaires, and documents were applied to the data collection. The result shows that implementing the InShot app gives EFL learners optimal stimulus in composing digital multimodal notices and developing their writing skills. It is manifested in their composition of digital multimodal notices reflecting complete generic structure, correct linguistic features, and matching images expressing the full meanings of the notices. Besides, they show positive responses. In this case, they are excited and interested in composing digital multimodal notices using the Inshot app. They combined appropriate colours, fonts, and backgrounds to create the meanings of the notices. The Inshot app facilitates learners to integrate the meanings presented in verbal, visual, and audio modes harmoniously, so the purpose of the notices is complete. However, learners with less digital literacy need help integrating the appropriate modes in composing digital multimodal notices.